A new history of Southeast Asia - Ricklefs, M. C.; Lockhart, Bruce; Lau, Albert; Reyes, Portia; Aung-Thwin, Maitrii (Palgrave Macmillan, 2010)
A new, comprehensive, one volume history of Southeast Asia that spans prehistory to the present. Ricklefs brings together colleagues at the National University of Singapore whose expertise covers the entire region, encompassing political, social, economic, religious, and cultural history.